Impacts of climate change on soil desiccation in planted forests with different tree ages: A case study in the Loess Plateau of China. (April 2023) - Li, Lanjun; Song, Xiaoyu; Feng, Dan; Li, Huaiyou; Zhao, Xinkai; Meng, Pengfei; Fu, Chong; Wang, Long; Jiao, Ruoyu; Wei, Wanyin; Yang, Nan; Liu, Yu
Graphical abstract: Highlights: Soil desiccation in four planted forests with different tree ages was simulated under combined climate change scenarios. Impacts of future climate on soil desiccation increased with tree ages in upper soil layers (0–40 cm), but decreased with them in lower soil layers (40–100 cm). Precipitation and vapor pressure deficit were the dominant climatic factors influencing soil desiccation in upper and lower layers, respectively. Tree age threshold for taking measures to control soil desiccation was unexpectedly delayed by 2a under future warming and drying climate. Abstract: Investigating the impacts of climate change on soil desiccation in planted forests is of theoretical and practical importance for water resource management and ecological restoration in the Loess Plateau. In this study, field experiments were conducted in four planted forests ( Platycladus orientalis plots) with tree ages of 5, 12, 25, and 35a (abbreviated as T5, T12, T25, and T35 plots, respectively). Based on which, Hydrus–1D models were calibrated and validated to simulate soil water dynamics under preset climate change scenarios. Then, the soil desiccation index ( SDI ) in different soil layers was calculated and evaluated. The results showed that under historical climate scenarios, soil desiccation levels were slight or medium in T5, T12, and T25 plots but were mainly medium or severe in T35 plots. Future warming and drying climate would greatly increase the SDI in all plots, and its impacts increased with tree ages in the upper soil layers (0–40 cm) but decreased with it in lower layers (40–100 cm). However, it only had limited influence on the responses of soil desiccation to the climate in different hydrological years. Precipitation and vapour pressure deficit dominated soil desiccation in the upper and lower layers, respectively, and both showed linear relationships ( p  < 0.05) with the SDI in corresponding soil layers. The SDI in the lower layers should be given full attention when controlling soil desiccation, and its rapid increase thresholds of tree ages were 20.3a under historical scenarios, but were unexpectedly delayed to 22.8a under future climate conditions. Our study not only improved the scientific understanding of the soil water conditions and their responses to climate change, but also provided valuable guidelines for the management of water resources and the restoration of the ecological environment in the semi-arid Loess Plateau.